Diversity of Helicobacter Pylori cagA and vacA Genes and Its Relationship with Clinical Outcomes in Azerbaijan, Iran - Mohammad Saeid Hejazi; Alka Hasani; Mohammad Reza Nahaei; Mohammad Taghi Akhi; Morteza Milani; Reza Ghotaslou; Mohammad Meshkini (Tabriz University of Medical Sciences, 2013)
Purpose: The purpose of this research was to analyze cagA and vacA genotypes status in H. pylori isolates and relationship with clinical outcomes. Methods: Gastric biopsy specimens were cultured for H. pylori isolation and cagA and vacA genes were detected in these isolates. Data were collected and the results were analyzed using χ2 and Fishers exact tests by SPSS software version. 16. Results: Of the total 115 H. pylori isolates, 79 (68.7 %) were cagA positive and 82 (71.3%) of isolates contained the s1 allele which 33 (28.7%) were subtype s2. s1m2 was the most frequent vacA allelic combination in the H. pylori isolates examined (63 cases), followed by s2m2 (31 cases), s1m1 (19 cases) and s2m1 (2 case). Strains cagA positive were more frequent in peptic ulcer diseases patients than non ulcer diseases patients, as 47 (59.5%) and 32 (40.5%), while cagA negative were low, as 15 (41.7%) and 21 (58.3%), respectively. Conclusion: We found that the cagA and vacA status were not related to clinical outcomes in this area. Overall, in the present study, vacA s1/m2, cagA-positive strains were predominant irrespective of clinical outcome, but s2/m1 was rare.